2019
DOI: 10.1021/acsnano.9b01392
|View full text |Cite
|
Sign up to set email alerts
|

Sn-Triggered Two-Dimensional Fast Protein Assembly with Emergent Functions

Abstract: The discovery of a general strategy for organizing functional proteins into stable nanostructures with the desired dimension, shape, and function is an important focus in developing protein-based self-assembled materials, but the scalable synthesis of such materials and transfer to other substrates remain great challenges. We herein tackle this issue by creating a two-dimensional metal−protein hybrid nanofilm that is flexible and costeffective with reliable self-recovery, stability, and multifunctionality. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 97 publications
0
29
0
Order By: Relevance
“…In recent years, protein‐based 2D assemblies have attracted attention, as many functional 2D protein crystals, such as bacterial S‐layer protein/crystal [ 33,34 ] and purple‐membrane assemblies, [ 55 ] have been found in nature. In the field of protein engineering, researchers have fabricated 2D free‐standing protein architectures by manipulating distinct chemical interactions between protein building blocks [ 11,56 ] and have designed de novo protein structures. [ 57 ] However, there are few reports about building 2D protein crystals at solid–liquid interfaces.…”
Section: Proteinsmentioning
confidence: 99%
“…In recent years, protein‐based 2D assemblies have attracted attention, as many functional 2D protein crystals, such as bacterial S‐layer protein/crystal [ 33,34 ] and purple‐membrane assemblies, [ 55 ] have been found in nature. In the field of protein engineering, researchers have fabricated 2D free‐standing protein architectures by manipulating distinct chemical interactions between protein building blocks [ 11,56 ] and have designed de novo protein structures. [ 57 ] However, there are few reports about building 2D protein crystals at solid–liquid interfaces.…”
Section: Proteinsmentioning
confidence: 99%
“…[109][110][111] In a study conducted by Saif et al, tin ion Sn 2+ was found for the first time to initiate rapid amyloid-like protein assembly by effectively reducing the disulfide bonds of lysozyme, and a multifunctional 2D Sn-doped lysozyme hybrid nanofilm was finally formed at the air/water interface (Figure 9a). [112] The area and thickness of the hybrid nanofilm could be controlled by the air/water interface size and protein concentration or reaction time. The high affinity of cystine residues to Sn 2+ played a crucial role in the coordination, stabilization, and rapid formation of the thermodynamically favored hybrid film.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…PTLF-HAp: The key challenge in the bone tissue engineering is to design and construct an interface with excellent bioactivity to support controllable and robust attachment of hydroxyapatite Reproduced with permission. [112] Copyright 2019, American Chemical Society. b) Fabrication of a freestanding protein-bound silver film.…”
Section: Wwwadvmatinterfacesde © 2020 Wiley-vch Gmbhmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, unlike self-assembled biopolymer structures in nature, the fabrication of a macroscopic 2D biopolymer material through economic supramolecular assembly remains a challenge, let alone the integration with AIEgens. [2][3][4][5]11,12 Secondly, the lack of a method to chemically or physically encode AIEgens into a 2D array of biopolymer chains further constrains the development of AIEgen@2D biopolymer materials. [1][2][3]13 Herein, we report sensitive binding of AIEgens to newlydeveloped amyloid-like suprastructures, which present the promising capability to synthesize highly emissive fluorescent 2D proteinaceous nanofilms, coatings and water-based inks.…”
Section: Introductionmentioning
confidence: 99%